When the Loss Costs Too Much: A Systematic Review and Meta-Analysis of Sarcopenia in Head and Neck Cancer - Hua, Xin; Liu, Shan; Liao, Jun-Fang; Wen, Wen; Long, Zhi-Qing; Lu, Zi-Jian; Guo, Ling; Lin, Huan-Xin (Frontiers in Oncology, 2020)
Purpose: Whether or not skeletal muscle mass (SMM) depletion, known as sarcopenia, has significant negative effects on the prognosis of patients with head and neck cancer (HNC) is both new and controversial. In this meta-analysis, we aimed to determine the prognostic significance of sarcopenia in HNC. Methods: We searched PubMed, the Cochrane Library, Embase, and Web of Science, which contains trial registries and meeting proceedings, to identify related published or unpublished studies. We used the Newcastle-Ottawa Scale (NOS) to appraise the risk of bias of the included retrospective studies. Pooled hazard ratios (HR) and the I2 statis-tic were estimated for the impact of sarcopenia on overall survival (OS) and relapse-free survival (RFS). Results: We analyzed data from eleven studies involving 2483 patients (39.4% on av-erage of whom had sarcopenia). Based on the univariate analysis data, the sarcopenia group had significantly poorer OS compared to the non-sarcopenia group (HR =1.97, 95% confidence interval [CI]:1.71-2.26, I2 = 0%). In the cut-off value subgroup, group 1, defined as skeletal muscle index (SMI) of 38.5 cm2/m2 for women and 52.4 cm2/m2 for men (HR =2.41, 95% CI: 1.72-3.38, I2 = 0%), had much poorer OS. In the race subgroup, the results were consistent between the Asia (HR = 2.11, 95% CI: 1.59-2.81) and non-Asia group (HR = 1.92, 95% CI: 1.64-2.25). The sarcopenia group also had significantly poorer RFS (HR = 1.74, 95% CI: 1.43-2.12, I2 = 0%). Conclusions: Presence of pre-treatment sarcopenia has a significant negative impact on OS and RFS in HNC compared with its absence. Further well-conducted studies with detailed stratification are needed to complement our findings. Keywords: Head and neck cancer; Sarcopenia; Meta-analysis; Prognostic factor